Strategic Analysis of Železiarne Podbrezová - Holubová, Petra (2023)
In this bachelor's thesis, the company Železiarne Podbrezová is the subject of an extensive strategic examination. Using techniques that cover both the macro and micro viewpoints, a multidimensional approach is employed in order to obtain insightful data on the enterprise's position within its industry. The PESTEL analysis, which outlines the political, economic, social, and technological landscapes, and Porter's five forces, which describes the bargaining power of buyers, bargaining powers of suppliers, the threat of substitute products, rivalry, and threats of new entrants landscapes, are used to unravel the macroenvironmental factors influencing the firm. The SWOT analysis is used to analyse the microenvironment while highlighting the company's innate strengths, weaknesses, opportunities, and threats. The VRIO framework allows for a deeper exploration of a company's internal resources, aiding in the identification of resources and competencies that may confer a lasting competitive advantage. By comparing the firm's performance measures with those of its rivals, benchmarking further contextualizes these conclusions. The study's main goal is to rigorously evaluate both the internal and exterior environment of Železiarne Podbrezová, guided by a thorough literature research. Finally, suggestions are created to set the direction for the business's future development initiatives using these analytical findings.